Imago, ius, religio. Religious Images in Medieval Legal Manuscripts: An Overview - Bilotta, Maria Alessandra; del Monaco, Gianluca (Eikón / Imago, 2023)
Editorial introduction to “Imago, ius, religio. Religious Iconographies in Illustrated Legal Manuscripts and Printed Books (9th-20th)”. The aim of this monographic issue is to analyse the use of religious iconographies in legal manuscripts and printed books, to create a basis for discussion and exchange on the diverse artistic, historical, and social aspects of these iconographies.